ISLAM DAN IDENTITAS - Muhammad Nursyahid (Universitas Islam Depok, 2021)
Identity is a visible display, attached to the individual. When Islam as a teaching is applied to individuals, cultural acculturation is born. There is an easily obtained tolerance, so rigidity is possible to avoid. That is ideal in theory. However, at the level of social practice, it is not easy to obtain. Negative sentiments are often expressed, when a community finds an individual who is different by